Factors influencing intraoperative and postoperative complication occurrence: A series of 1135 periodontal and implant‐related surgeries - Gary M. Blyleven; Thomas M. Johnson; Kimberly Ann Inouye; Brian W. Stancoven; Adam R. Lincicum (Wiley, 2024)
Abstract Objectives In periodontology, it is widely recognized that evidence characterizing the incidence and effect of treatment complications is lacking. The objective of this study was to assess the influence of operator‐, procedure‐, patient‐, and site‐associated factors on intraoperative and postoperative complication occurrence. Material and Methods A single investigator reviewed records of patients treated by eight periodontics residents from July 2018 through June 2022. For each procedure, the investigator recorded each intraoperative and postoperative complication or indicated that no complication had occurred. These outcomes were analyzed against a panel of explanatory covariates. In addition, the severity of each postoperative complication was assessed using a standardized grading system. Results A total of 1135 procedures were included in the analysis. Intraoperative and postoperative complications were identified in 2.8% and 15.2% of procedures, respectively. The most common intraoperative complications were Schneiderian membrane perforation (1.3%) and gingival flap perforation/tear (1%), and the most common postoperative complications were dentin hypersensitivity (2.6%), excessive pain (2.5%), and infection (2.2%). Subepithelial connective tissue graft (odds ratio [OR]: 3.2, 95% confidence interval [CI]: 1.6, 6.1; p < .001), guided bone regeneration (OR: 3.0, 95% CI: 1.4, 6.5; p = .004), and guided bone regeneration with implant placement (OR: 3.1, 95% CI: 1.3, 7.6; p = .011) were associated with higher odds of postoperative complication, whereas lateral sinus elevation (OR: 102.5, 95% CI: 12.3, 852.9; p < .001), transalveolar sinus elevation (OR: 22.4, 95% CI: 2.2, 224.5; p = .008), open flap debridement (OR: 36.4, 95% CI: 3.0, 440.7; p = .005), and surgically facilitated orthodontic therapy (OR: 20.5, 95% CI: 1.2, 358.4; p = .039) were associated with higher odds of intraoperative complication occurrence. Conclusions Consistent with previous reports, procedure type appears to be the predominant factor driving complication occurrence. As analyses of treatment complications increase, individualized risk‐benefit assessments will become progressively meaningful for patients.